Optimization of qPCR assay of chicken cytokine genes using sybr green method - Chan, Jia Hui (2015)
Quantitative PCR (qPCR) has been widely utilized in the study of cytokine expression profile upon vaccination of recombinant fowlpox virus and challenge of avian influenza virus. Although Taqman qPCR method offers specific detection of amplified products, SYBR green qPCR is more cost effective and relatively reliable to be used in expression profiling. In this study, total RNA samples were first harvested from spleens of two-week-old control chickens before reverse-transcribed to cDNA using iScript Supermix, with minor modifications. Sensitive qPCR assays based on real-time analysis of amplified products, intercalated with SYBR Green I dyes were designed and optimized using specific pairs of primers, to quantify chicken IL-15, IL-12, IL-18 and IFN-γ cytokine expressions. Amplification efficiency and coefficient of determination (R2) were calculated by Bio Rad CFX Manager Software after a linear standard curve was generated. From the findings, qPCR assays of two chicken cytokine genes, IL-15 and IL-18, and two housekeeping genes, GAPDH and β-actin, were successfully optimized. Optimal annealing temperature of IL-15, IL-18, and β-actin were 59˚C, while GAPDH was 64˚C. Amplification efficiencies of those genes were within the ideal range, which is 95%-105%. R2 values of those genes were also higher than 0.98 (>0.98). Melt-curve analysis of those genes showed that there was only one significant peak which corresponded to single specific amplified product. However, no result was obtained for cytokines IL-12 and IFN-γ. With the optimized amplification condition and annealing temperature of qPCR assays of each cytokine, differences of cytokine expression between control and vaccinated chicken can be studied in future work.